Reflexive pedagogical practice and formation of human capacities from the Franciscan pedagogy - Guerrero Lucero , Maura Andrea; Rodríguez Ortiz, Diego Alexander (SATHIRI, 2023)
The article presents some results of a research carried out at the Mariana University, Pasto, in order to contribute to alternatives to mitigate the mechanization of pedagogical practice and favor reflection on it; This study was carried out with the participation of teachers representing 19 undergraduate programs, through the strategy called "Community of Practice", with whom field diaries, self-portraits, workshops and piloting of the application in the microcurriculum of the skills courses were developed. of being, built collectively, guided by the project participants in period 1 of 2021. The study was carried out under the qualitative approach, with the methodology of Pedagogical Action Research (IAP), in three (3) phases: Deconstruction, Reconstruction and Evaluation of the reconstructed. The information obtained was organized by deductive and inductive categories. Among the results, the possibility of resignifying the pedagogical practice from reflexive processes around the Franciscan pedagogy and the human capacities approach stands out, as well as the conceptual and motivational transitions of the participating teachers, after delving into the proposed categories and to apply, in their practice, competences of being, built in a community of practice, to finally establish the stages and the route for the implementation of the CAPAZER Model at the Mariana University.